2 x ao quadrado + 2x - 12 = 0
![2 {x}^{2} + 2x - 12 = 0 2 {x}^{2} + 2x - 12 = 0](https://tex.z-dn.net/?f=2+%7Bx%7D%5E%7B2%7D++%2B+2x+-+12+%3D+0)
Soluções para a tarefa
Respondido por
0
Resposta:
S = {- 3, 2}
Explicação passo-a-passo:
2x² + 2x - 12 = 0 (÷2)
x² + x - 6 = 0
a: 1 b: 1. c: - 6
∆ = 1² - 4 • 1 • (- 6)
∆ = 1 + 24
∆ = 25
x = [- 1 +- √25]/2 • 1
x = [- 1 +- 5]/2
x' = [- 1 + 5]/2
x' = 4/2
x' = 2
x" = [- 1 - 5]/2
x" = - 6/2
x" = - 3
S = {- 3, 2}
Bons estudos!!!
Perguntas interessantes
Espanhol,
10 meses atrás
Ed. Técnica,
10 meses atrás
História,
10 meses atrás
Biologia,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás